Capital Flight and Violent Conflict-A Review of the Literature - Davies, Victor A.B. (Washington, DC: World Bank, 2012)
Reviews the literature on what happens to capital flight before, during, and after violent conflict and its implications for post-conflict economic recovery since by the end of the conflict a considerable amount of capital could have accumulated abroad. Capital flight refers to outflows of private capital from developing countries and is viewed as 'hot money' fleeing political and financial crisis, heavier taxes, capital controls, currency devaluation, or hyperinflation. Issues concern how to measure capital flight with multiple measures proposed depending on whether the estimator deems it a flow or stock. Capital flight is often studied as a portfolio-choice decision relative to a risk-adjusted expected return, which violent conflict directly affects by increasing the riskiness of the domestic environment, reducing risk-adjusted expected return, and thereby inducing capital flight. Indirectly, violent conflict affects the portfolio-choice framework by its impact on inflation and public debt. For countries facing much higher wartime inflation rates, much bigger reductions in capital flight could be realized through larger cuts in inflation.